The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12877-022-02871-5
|View full text |Cite|
|
Sign up to set email alerts
|

External validation of a new predictive model for falls among inpatients using the official Japanese ADL scale, Bedriddenness ranks: a double-centered prospective cohort study

Abstract: Background Several reliable predictive models for falls have been reported, but are too complicated and time-consuming to evaluate. We recently developed a new predictive model using just eight easily-available parameters including the official Japanese activities of daily living scale, Bedriddenness ranks, from the Ministry of Health, Labour and Welfare. This model has not yet been prospectively validated. This study aims to prospectively validate our new predictive model for falls among inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…14 Our previous studies revealed different results for the association between each factor and falls, which might be caused by different backgrounds of the study populations (ie, degree of cognitive impairment, age, primary illness on admission, and type of hypnotic medications prescribed) as well as different study periods. 14,18 Among those factors, our studies indicated the significance of BRs whereas other previous studies have also shown permanent residual damage from a previous stroke or a history of falls as factors associated with falls. 14,[18][19][20][21] Revealing the association between BRs and falls will highlight the usefulness of BRs in predicting falls, which may lead to developing a better and more accurate approach for predicting falls using BRs.…”
Section: Introductionmentioning
confidence: 41%
See 3 more Smart Citations
“…14 Our previous studies revealed different results for the association between each factor and falls, which might be caused by different backgrounds of the study populations (ie, degree of cognitive impairment, age, primary illness on admission, and type of hypnotic medications prescribed) as well as different study periods. 14,18 Among those factors, our studies indicated the significance of BRs whereas other previous studies have also shown permanent residual damage from a previous stroke or a history of falls as factors associated with falls. 14,[18][19][20][21] Revealing the association between BRs and falls will highlight the usefulness of BRs in predicting falls, which may lead to developing a better and more accurate approach for predicting falls using BRs.…”
Section: Introductionmentioning
confidence: 41%
“…14,18 Among those factors, our studies indicated the significance of BRs whereas other previous studies have also shown permanent residual damage from a previous stroke or a history of falls as factors associated with falls. 14,[18][19][20][21] Revealing the association between BRs and falls will highlight the usefulness of BRs in predicting falls, which may lead to developing a better and more accurate approach for predicting falls using BRs. However, we performed stratified analyses on patients who had some items not used in the SFRM-2 in our former validation study.…”
Section: Introductionmentioning
confidence: 41%
See 2 more Smart Citations
“…After publication of this article [ 1 ], the authors reported that there was a mistake in the formula of model 2 in Additional file 3. The correct formula of model 2 is as follows:…”
mentioning
confidence: 99%